Cultural Da'wah Values in the New Year's Work Tradition in Gurusinga Village - Rini Mayang Sari; Sahrul Sahrul (Edusoshum : Journal of Islamic Education and Social Humanities, 2026)
This research aims to analyze the cultural preaching values contained in the Year-End Work Tradition in Gurusinga Village, Berastagi District, Karo Regency, and to identify the challenges in its implementation. The research uses a qualitative approach with a case study design. Data were collected thru participatory observation, semi-structured in-depth interviews, and documentation from village heads, customary leaders, Islamic religious leaders, organizing committees, community leaders, and community members actively participating in the Yearly Work Tradition. Data analysis was conducted using the interactive model of Miles, Huberman, and Saldaña, while data validity was tested thru source, technique, and time triangulation. The research results show that the Year-End Work Tradition is still preserved as a cultural heritage of the Karo community, which functions to strengthen social cohesion thru deliberation, mutual assistance, and active participation of the community across ethnicities and religions. This tradition contains cultural preaching values that include gratitude to Allah Swt., brotherhood, mutual cooperation (ta'awun), interfaith tolerance, social concern, and the preservation of local culture. These values are internalized thru cultural practices that shape the religious character and social solidarity of the community. However, the implementation of cultural da'wah still faces challenges, including the provision of food that adheres to halal principles, the influence of modernization on the younger generation's understanding of traditional values, and the need for harmonization between cultural preservation and the application of Islamic values.